The effect of air pollution quality on lung cancer rates in middle-income and high-income countries: a panel data analysis approach - Gozlu, Mehmet; Senol, Osman; Cirakli, Umit; Aslan, Huseyin; Akbulut, Fevzi; Gokkaya, Durmus (Frontiers in Public Health, 2024)
Background: Air pollution is one of the biggest problems in societies today. The intensity of indoor and outdoor air pollutants and the urbanization rate can cause or trigger many different diseases, especially lung cancer. In this context, this study's aim is to reveal the effects of the indoor and outdoor air pollutants, and urbanization rate on the lung cancer cases.Methods: Panel data analysis method is applied in this study. The research includes the period between 1990 and 2019 as a time series and the data type of the variables is annual. The dependent variable in the research model is lung cancer cases per one hundred thousand people. The independent variables are the level of outdoor air pollution, air pollution level indoor environment and urbanization rate of countries.Results: In the modeling developed for the developed country group, it is seen that the variable with the highest level of effect on lung cancer is the outdoor air pollution level.Conclusions: In parallel with the development of countries, it has been determined that the increase in industrial production wastes, in other words, worsening the air quality, may potentially cause an increase in lung cancer cases. Indoor air quality is also essential for human health; negative changes in this variable may negatively impact individuals' health, especially lung cancer.